The Ethnobiology of Absurdities (Ethnobiology and Conservation, 2024)
We are often overwhelmed by a sense of frustration when we observe that certain social issues, rather than progressing, seem to stagnate or even worsen–a rise in violence against women, racism, misogyny, and transphobia. These problems, far from disappearing, raise the question of whether we truly advance toward a higher state of civility or are trapped in an endless cycle of setbacks. The feeling that progress is illusory and fleeting leads us to reflect deeply on the state of science, particularly ethnobiology.